Is there a gender difference in the ability to deal with failures? Evidence from professional golf tournaments - Olof Rosenqvist (Institute for Evaluation of Labour Market and Education Policy (IFAU), 2016)
Recent experimental evidence suggests that women in general are more discouraged than men by failures which potentially can explain why women, on average, are less likely than men to reach top positions in firms. This paper provides the first quasi-experimental evidence from the field on this issue using data from all-female and all-male professional golf tournaments to see if this result can be replicated among competitive men and women. These top-performing men and women are active in an environment with multiple rounds of competition and the institutional set-up of the tournaments makes it possible to causally estimate the effect of the result in one tournament on the performance in the next. The results show that both male and female golfers respond negatively to a failure and that their responses are virtually identical. This finding gives support to the hypothesis that women's difficulties in reaching top positions in firms are caused by external rather than internal barriers, but does of course not rule that other internal barriers may be present for women.
Keywords: J16; J24; L83; C93; 330; glass ceiling; failure; gender; regression discontinuity design; golf